The influence of inter-annual temperature variability on the Greenland Ice Sheet volume - Mikkel Lauritzen; Guðfinna Aðalgeirsdóttir; Nicholas Rathmann; Aslak Grinsted; Brice Noël; Christine S. Hvidberg (Annals of Glaciology)
The Greenland Ice Sheet has become an increasingly larger contributor to sea level rise in the past two decades and is projected to continue to lose mass. Climate variability is expected to increase under future warming, but the effect of climate variability on the Greenland Ice Sheet volume is poorly understood and is adding to the uncertainty of the projected mass loss. Here we quantify the influence of inter-annual temperature variability on mass loss from the Greenland Ice Sheet using the PISM model. We construct an ensemble of temperature-forcing fields that accounts for inter-annual variability in temperature using reanalysis data from NOAA-CIRES over the period 1851–2014. We investigate the steady-state and transient response of the Greenland Ice Sheet. We find that the simulated steady-state ice-sheet volume decreases by 1.9 ± 0.4 cm of sea level equivalent when forced with a varying temperature forcing compared to a constant temperature forcing, and by 11.5 ± 1.4 cm when the variability is doubled. The northern basins are particularly sensitive with a change in volume of 0.9–1.1%. Our results emphasize the importance of including temperature variability in projections of future mass loss.